2016
DOI: 10.1016/j.dld.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes with lanreotide Autogel/Depot for carcinoid syndrome: An international observational study

Abstract: Lanreotide treatment was associated with improvements in symptoms as well as a range of PROs in patients with neuroendocrine tumours and carcinoid syndrome (ClinicalTrials.gov: NCT01234168).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…Furthermore, a proportion of patients with time, especially patients with F-NETs with nongastrinoma, insulinoma syndromes, treated with somatostatin analogues, develop increasing resistance with time, when used at conventional doses[9498]. Numerous studies, especially in patients with the carcinoid syndrome or VIPomas, have reported that increasing the doses of the somatostatin analogues by either using a higher dose, or using a conventional dose, at increased frequency than is conventionally used (more frequent than 1x/month) can help control the hormone-excess symptoms[94, 95, •96, 97102]. …”
Section: Summary Of Recent Advances/controversies In Management Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, a proportion of patients with time, especially patients with F-NETs with nongastrinoma, insulinoma syndromes, treated with somatostatin analogues, develop increasing resistance with time, when used at conventional doses[9498]. Numerous studies, especially in patients with the carcinoid syndrome or VIPomas, have reported that increasing the doses of the somatostatin analogues by either using a higher dose, or using a conventional dose, at increased frequency than is conventionally used (more frequent than 1x/month) can help control the hormone-excess symptoms[94, 95, •96, 97102]. …”
Section: Summary Of Recent Advances/controversies In Management Ofmentioning
confidence: 99%
“…Long acting somatostatin analogues(Octreotide-LAR, Lanreotide-autogel) supplemented during break-through with subcutaneous octreotide, are the standard therapies for controlling the principal carcinoid syndrome symptoms of diarrhea, flushing, and asthma[2, •96, 98, •120, 145, •146]. With time, refractory cases may develop and therefore, there is a need for new treatments[2, •96, 98, •120, 145, •146].…”
Section: Summary Of Recent Advances In Management Of Specific Hormmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Satisfaction with diarrhea control and flushing control and a good impact on the quality of life have also been reported in an open-label observational study (Table 2). 55 Moreover, the once-monthly dosing regimen of LAN is associated with improved patient adherence and patient perception of LAN injection 56,57…”
Section: Use Of Lan Autogel In Gep-nensmentioning
confidence: 99%